2024
DOI: 10.1002/smll.202312238
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Wearable Sensor Based on (001)‐Orientated TiO2 for Real‐Time Electrochemical Detection of Dopamine, Tyrosine, and Paracetamol

Tianyao Zhang,
Jia Zhu,
Maowen Xie
et al.

Abstract: The concentration of dopamine (DA) and tyrosine (Tyr) reflects the condition of patients with Parkinson's disease, whereas moderate paracetamol (PA) can help relieve their pain. Therefore, real‐time measurements of these bioanalytes have important clinical implications for patients with Parkinson's disease. However, previous sensors suffer from either limited sensitivity or complex fabrication and integration processes. This work introduces a simple and cost‐effective method to prepare high‐quality, flexible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Dopamine (DA), an essential neurotransmitter, plays a pivotal role in a multitude of physiological functions, which include neural signaling, extracerebral vasodilation, and the process of reward in the brain. As the importance of the neurotransmitter DA in cognitive function and emotion regulation is gradually being recognized, the need for noninvasive continuous monitoring of its dynamic changes is becoming increasingly urgent. , A method for electrochemical monitoring of single-atom manganese-doped MoS 2 enabling ultrasensitive detection of dopamine was reported by Lei et al Another interesting work was reported by Duru et al on the use of spatially resolved microarray electrodes to achieve local pH polymerization of the DA reaction for visual monitoring of DA . Although a number of high-performance electrochemical monitoring programs have been developed, traditional methods are often limited by complex equipment, restrictive operations, and invasive methods.…”
mentioning
confidence: 99%
“…Dopamine (DA), an essential neurotransmitter, plays a pivotal role in a multitude of physiological functions, which include neural signaling, extracerebral vasodilation, and the process of reward in the brain. As the importance of the neurotransmitter DA in cognitive function and emotion regulation is gradually being recognized, the need for noninvasive continuous monitoring of its dynamic changes is becoming increasingly urgent. , A method for electrochemical monitoring of single-atom manganese-doped MoS 2 enabling ultrasensitive detection of dopamine was reported by Lei et al Another interesting work was reported by Duru et al on the use of spatially resolved microarray electrodes to achieve local pH polymerization of the DA reaction for visual monitoring of DA . Although a number of high-performance electrochemical monitoring programs have been developed, traditional methods are often limited by complex equipment, restrictive operations, and invasive methods.…”
mentioning
confidence: 99%